Determinants of Micro Enterprises Business performance in Malaysia: A systematic literature review - Abdul Aziz, Nor Aidil; Abu Bakar , Hatinah; Burdhan, Wan Nur Nalisa (International Journal of Accounting, Finance and Business, 2025)
The objective of this study is to review articles of the determinants of micro enterprises’ business performance from 2010 to 2024. The PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method was utilized to classify the articles in which fifteen (15) articles related to the study were identified. The findings showed that numerous articles were found in the Scopus database with the highest publications being conducted in China and the most common study design was quantitative type of approach. Among the factors that are found to be the determinants of micro enterprises’ business performance are external factors such as financial support, government policies, regulatory environment, economic conditions and internal factors such as firms’ characteristics, entrepreneur orientation, innovation and technology, marketing orientation, strategic orientation and financial